Off-loading total contact cast in combination with hydrogel and foam dressing for management of diabetic plantar ulcer of the foot - Tanawat Vaseenon (2018)
© 2014, Medical Association of Thailand. All rights reserved. Background: The total contact cast is considered to be an effective method of off-loading a diabetic non-infected pressure ulcer. However, complications have been reported in 1 to 15% of cases, e.g. prolonged healing of the ulcer. Debridement with modern dressings has been reported to be effective in promoting wound healing; however, there have been few reported studies of the combination of modern dressings with the cast. Objective: To evaluate the effectiveness of a combination of treatments on healing rates in diabetic non-infected plantar ulcer of the foot. Material and Method: This retrospective study with prospective data collection was conducted between September 2010 and August 2012. Twenty diabetic patients with plantar neuropathic ulcer were treated using a combination of a contact cast plus hydrogel and foam dressings. The size and location of the ulcer, ulcer healing, foot deformities and complications were evaluated. Results: Of 21 ulcers, 20 (95.2%) healed completely in a mean time of 30.1 days (range 14 to 70 days). Healing times for forefoot and midfoot ulcers were 22.6 and 26.8 days, respectively, which is significantly shorter than the 51.7 days for heel ulcers. One patient who had an unhealed ulcer developed a severe infection two months after treatment, which necessitated below the knee amputation. There were three cases of recurrence of the ulcers after casting. Conclusion: Off-loading casting combined with modern dressings had a high rate of healing in short-term treatment of diabetic non-infected pressure ulcers. Recurrence of ulcers and new site abrasions were common complications; those complications may have been caused by association with bone deformity or improper footwear.